Fluid mechanics with engineering applications - Franzini, Joseph B.; Finnemore, E. John. (New York : McGraw-Hill, 1997)
This book is about: Properties of fluids; Fluid statics; Basics of fluid flow; Energy considerations in steady flow; Momentum and forces in fliud flow; ...
Keywords: Engineering; Fluid mechanics; Fluid mechanics